Efforts to Improve Teacher Performance: A Theoretical Review - Novita Anggraeni (Green Publisher Indonesia, 2021)
This article describes about improving teacher performance from the point of view of teacher performance. The writing of this article uses descriptive analytical methods by reviewing the literature on teacher performance theory. Based on this study four conclusions were found: (a) Teachers are one component of education that play an important role in the success of education, teachers are expected to be able to play the role of ideal teachers. (b) Improving teacher performance is one way to improve the quality of education. (c) Teacher performance is the teacher's perception of teacher's work performance related to the quality of work, responsibility, honesty, cooperation and work results. (d) Several factors that influence teacher performance include: (1) the principal's leadership role, (2) personal relationships between peers, (3) teacher-controlled competencies, (4) good training and development of Teacher Resources (HR). Teachers have an important role as a determinant of the success of a quality learning process. Therefore, efforts are needed to improve teacher performance to know their roles and functions so that educational goals can be achieved.